Framework for CORECA action - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The document was written to provide a broader and clearer understing of IICA's purposes and those of the Council, and of the executive activities carried out by the Secretariat, in light of the new agreement on Technical Cooperation between the countries and IICA. It refers to the basis of IICA's cooperation with CORECA, its regional emphasis, and its general operational and strategic framework.